Web-Based Information System and Messaging at Boarding House Gang Famili No.03 Sei Sikambing Cii - Alfonsus Situmorang, Ricky; Putra, Eka; Hendry (Cattleya Darmaya Fortuna, 2025)
Rumah Kost Gang Famili No. 03 is one of the residences that has been established since 1991 and has served tenants for a long time. In its management, the process of recording tenant data, payment, and communication between boarding house owners and tenants is still carried out manually, so there are often delays in information and lack of efficiency. This research aims to design and develop a web-based information system for Rumah Kost Gang Famili No.03 with the Waterfall method, which is integrated with a messaging system (WhatsApp or SMS notifications) to facilitate the administration, monitoring, and communication process. This system has two types of users, namely visitors (tenants) who can view information and contact admins, and admins who can manage the webside itself. With the implementation of this system, it is hoped that boarding house management will be more effective, efficient, and responsive to the needs of tenants.